G247 Role of the deprivation of liberty process in specialist paediatric neurorehabilitation practice. (May 2019) - Murgan, A; Eve, M; Sharples, PM
Abstract : Introduction: In adult neurorehabilitation practice, understanding of legislation underpinning Deprivation of Liberty is a quality standard for specialist services. However, consultant paediatricians involved in specialist neurorehabilitation may be unfamiliar with this concept. We present the case of a 16-year-old patient who sustained severe cognitive impairment following traumatic brain injury (TBI), received in-patient neurorehabilitation in our unit until age 17, and for whom Deprivation of Liberty legislation was highly relevant. Case description: The patient sustained multiple injuries in a road traffic accident, including severe TBI. Previously she was well, with above- average cognition, but a history of self-harm, oppositional behaviour and substance abuse. She was in local authority foster placement (Section 20) at the time of the accident. Three months post-TBI, she had made a good physical recovery but had severe cognitive impairment, particularly involving domains of attention, memory and executive function. She was deemed extremely vulnerable, especially in view of her complex social background. She was therefore not permitted to leave the hospital, except under close supervision, nor to access the internet unsupervised. In view of her age and significant restrictions, Deprivation of Liberty safeguards were considered applicable. Regular assessments under the Mental Capacity Act were performed, to determine if she had the capacity to keep herself safe outside hospital, implying capacity to self-discharge, and whether she had capacity to keep herself safe online. Despite improved cognitive functioning, she continued to lack capacity in these regards throughout her in-patient stay and restrictions remained in place. An application was made to the Court of Protection to sanction Deprivation of Liberty. Discussion: At present, the standard Deprivation of Liberty legal process is only applicable to adults aged 18 years or older, although this is under review. It is likely there are other cases in the UK involving young people aged 16–17 years with cognitive impairment receiving in-patient neurorehabilitation where it may be appropriate to apply Deprivation of Liberty safeguards, including assessment of Mental Capacity, and consider application to the Court of Protection. We propose awareness of the Deprivation of Liberty process and evidence of related local protocols should be a quality standard for specialist paediatric neurorehabilitation units.